Ferdinand de Saussure: de silêncio e de autoria - Vinhais, Eminéa Aparecida (2012)
This paper has the purpose to, initially, discuss a reflection about Ferdinand de Saussure s silence, a Swiss linguist, considered the father of modern linguistics and structuralism, and also to question some occurrences, such as the non-publication of the Course in General Linguistics or his researches, tested by the manuscripts; also the fact that Saussure had not said to his students the content of the manuscripts, where he reflected and wrote his researches; in addition to the reason that the linguist has been self credited thirty years of silence. The concerns around this Saussure silence allowed the focus of this research to direct to two questions: the authorship of the book, once the Course in General linguistics was edited by Saussure s students, Bally and Sechehaye (1916), and the dislocation of the silence of Saussure to the silence in Saussure, in the sense that his manuscripts contained blank parts, the erasures and the hiatus, besides the theorization of the Course in General Linguistics present another form of silence. These analysis, have been supported by a psychoanalytic perspective of the unconscious subject, in accordance with Freud and Lacan. Therefore, concerning Saussure s authorship of the Course in General Linguistics, the intention to overtake the naive notion about the author, seeing the three courses that Saussure realized in Geneva as one of his last theoretical demarche, the existence of the book as a result of the students commitment with the teacher theorization, and the illusion of questioning the legitimacy of the book in relation to Saussure s exact words. Concerning the focus on the silence in Saussure, distinguished by Lacan s view, the taceo silence, which is referred to what is not said, and the sileo, which is the silence related to the instinct (or drive). From this distinction, we have researched on Saussure s manuscript and the Course in General Linguistics, if there would have a Saussure s silence related to the theorization about speech (parole) or, yet if the theories about language (langue), specially the linguistic sign and the linguistic value, present in the Course in General Linguistics and in the Writings in General Linguistics, would be related to any type of silence. The analysis indicated the sileo silence, in the sense that it is constitutive of Saussure s form of production; it is present in its own theorization, once it generates other theory productions, so that sileo, instead of pointing the end of his theory, demonstrates in advance the movement of his elaboration. Finally, the reflections had the purpose of overpassing the most common sense of the authorship and of silence, proposing a specific discussion about Saussure s theorization, the Course in General Linguistics, the editors, and his manuscripts, in order to indicate that both works are very important to the general sciences, and that the constitutive silence found in the saussurian theorization, indicates the presence of Saussure and, therefore, his authorship.